Aquinum, un caso di studio da manuale : Dalla fotointerpretazione archeologica al rilevamento di prossimità dei paesaggi storici in Etruria e Sicilia - Ceruado, Giuseppe (GEOmedia, 2024)
This contribution, without the presumption of outlining the guidelines of the field, aims to stimulate debate and discussion on the operational choices applied or applicable in different areas of Ancient topography investigations, with particular attention to the refinements of research, study methods, and tools used. All of this is achieved through the presentation of the case study of Aquinum, a Roman colony in South Latium, highlighting direct experiences conducted in the field to illustrate the strategic project and its corresponding results, avoiding abstract theorizations.